Biodiversity and community assemblages of freshwater and marine macrozoobenthos in Gorontalo Waters, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Kadim MK, Pasisingi N, Alinti ER, Alinti ER, Panigoro C. 2022. Biodiversity and community assemblages of freshwater and marine macrozoobenthos in Gorontalo Waters, Indonesia. Biodiversitas 23: 637-647. Macrozoobenthos plays an essential role in the aquatic ecosystem including as primary consumers, food sources, and water quality bioindicators. This study aimed to determine the composition, taxa abundance, community structure of the macrozoobenthos in the lower reach, estuary, and marine areas along Gorontalo waters, also their association with water quality parameters. Biota samples were collected purposively from 33 sampling points. The sampling process was conducted in June 2020 and May 2021. Macrozoobenthos samples were taken using Ekman Grab and prepared with filters (mesh size of 500 µm). Statistically, a t-test was done to assess the significance of taxa abundance difference among three different ecosystems from both sampling periods. Similarity percentages were displayed through a dendrogram. Furthermore, the biota assemblages and water quality parameters association were interpreted through Eigenvalues of Principal Component Analysis using Minitab ver. 14.0. The results showed that the macrozoobenthic community structure composed 70 taxa belonging to six classes dominated by Gastropoda, followed by Bivalvia, Malacostraca, Clitellata, Polychaeta, and Polyplacophora. The marine area had the highest abundance of macrozoobenthos (469.5 ind. m-3 in 2020; 460.9 ind. m-3 in 2021), followed by the river station (335.3 ind. m-3 in 2020; 2621 ind. m-3 in 2021), and estuary zone (217.3 ind in 2020. m-3; 848.5 ind. m-3 in 2021). The most abundant species in the lower reach area was Melanoides sp. (135.5 ind. m-3 in 2020; and 1222.5 ind. m-3 in 2021), while in the estuary was Brachidontes sp. (70.7 ind. m-3 in 2020; and 248 ind. m-3 in 2021). Batillaria sp. (128.3 ind. m-3 in 2020) and Anachis sp. (1510.7 ind. m-3 in 2021) were the species with the highest number in the marine zone. Based on the diversity and evenness index, the sea was in the medium category with no dominant species in the marine area. Biota communities in the lower reach station tend to be more like estuary biota than marine biota.
Keywords: Community structure, Gorontalo Bay, macrozoobenthic, Principal Component Analysis, Tomini Bay